Evolution of whole society participation in AIDS prevention and control in China: a brief discussion - Quan SUN; Jun-qi CHENG; Xiao-jun XU (Editorial Office of Chinese Journal of Public Health, 2022)
Recognizing AIDS epidemic as a social problem, the article reviews the development process of society participation in AIDS prevention in China during the past 40 years from a panoramic perspective. During the period in China, the concept of AIDS prevention changed from prevention and treatment to prevention and control with a passivity to initiative transformation occurring in the development of whole society participation in AIDS containment. From a long-term consideration, the initiative of whole society participation in AIDS prevention and control needs to be promoted continuously for the construction of a prevention community for effective control of AIDS epidemic.